Prática antropológica em processos de regularização de territórios quilombolas: o antropólogo no INCRA - CARDOSO, Michael Jackson Miranda (2018)
The text presented here represents an attempt to analyze the work of the anthropologist in the scope of the official processes of recognition and identification of the lands occupied by "remnants of quilombos communities", dealt with in Art. 68 of ADCT. It has the objective of elaborating an ethnography of the anthropological work, from our professional insertion as an anthropologist in the Regional Superintendence of the National Institute of Colonization and Agrarian Reform (INCRA) in Maranhão (SR12-MA). The anthropological work is something that has been characterized by a method consecrated in the anthropological discipline, the participant observation in the context of the intensive fieldwork with the researched groups. It is constituted as a habitus (BOURDIEU, 2000) that is structured by the practice of fieldwork, the dedication to know the so-called primitive societies, the exotic, the native, the other, the distant societies. On the other hand, this experience of detachment, of being "there" with "them", can also be realized in the researcher's own society. As Da Matta (1978) states, to do anthropology is to transform the exotic into the familiar and the exotic into the exotic. From this relativization movement of our own place, we can also make an anthropology of ourselves. From this perspective, the exercise we propose is to reflect on our own performance in the processes of regularization of the quilombola territories because we perceive that here opens a space of interesting discussion about the conditions of the anthropological work and its scientific support. When speaking in anthropology of the practice, I understand it in the sense attributed by Cardoso de Oliveira, of the professional anthropologist who exercises interventionist actions. To accomplish this work, I conducted semistructured interviews with INCRA's staff in Maranhão. Also analyzed were administrative processes and Anthropological Reports referring to the recognition and identification of "remnants of quilombos communities" with demand for land regularization in the incra superintendence in Maranhão, as well as my own impressions as a professional involved in this context of action.